Lee-Palfrey families papers - Kalisky, Louisa, active 1823-1827.; Lee, Susan Palfrey, 1767-1822.; Lee, William, 1772-1840.
Correspondence, diaries, journals, clippings, maps, photographs, and other papers of William Lee (1772-1840) of Boston, Mass., Washington, D.C., and France and of other Lee family members. Lee's correspondence and diaries detail his experiences as a commercial agent and secretary to the U.S. Legation in France. Also includes papers of Lee's wife Susan Palfrey Lee (1767-1822) relating to family matters and social life in Washington, D.C., and France; papers of his daughters, Susan Palfrey Lee (1795-1853) and Mary Elizabeth Lee, Baroness de Maltitz, and of his son, William Barlow Lee; a journal of William Barlow Lee's son William Lee (1841-1893) relating to a topographical survey mission to Utah in 1857 and 1858; an incomplete translation of a German diary (1823-1827) of Louisa Kalisky; and papers of Palfrey family members.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English, with French.
Keywords: Lee family; Palfrey family; United States. -- Legation (France); Diplomatic and consular service, American -- France; Topographical surveying -- Utah; France -- Commerce -- United States; France -- Foreign relations -- United States; France -- Social life and customs; United States -- Commerce -- History -- 19th century; United States -- Commerce -- France; United States -- Foreign relations -- France; Utah -- Description and travel; Washington (D.C.) -- Social life and customs; Lee, Susan Palfrey, -- 1795-1853.; Lee, William, -- 1841-1893.; Lee, William Barlow, -- 1805-1895.; Maltitz, Mary Elizabeth Lee, -- Baroness de, -- 1799-1852.